Effects of shift work on sleep quality of policemen : A systematic review Efeitos do Trabalho em Turnos na Qualidade do Sono de Policiais: Uma Revisão Sistemática - Bernardo V.M.* (2015)
© 2015, Editorial Ciencias Medicas. All rights reserved.The sleep quality of police is an important marker for quality of life and development of their professional activities. Thus, this study aimed to summarize the scientific literature on the effects of shift work on sleep quality of police through a systematic literature review. So the MEDLINE via PubMed, CINAHL and SCOPUS databases and articles identified through a manual search were used. The search strategy included the following descriptors related to shift work: “Shift-Work Sleep Disorder” OR “Shift-Work Sleep Disorders” OR “Sleep Disorders, Shift-Work” OR “Sleep Disorder, Shift-Work” OR “Sleep Disorder, Shift Work” OR “Shift Work”; to sleep: "Sleep Deprivation"[Mesh] OR “Deprivation, Sleep” OR “Deprivations, Sleep” OR “Sleep Deprivations” OR “REM Sleep Deprivation” OR “Deprivation, REM Sleep” OR “Deprivations, REM Sleep” OR “REM Sleep Deprivations” OR “Sleep Deprivation, REM” OR “Sleep Deprivations, REM” OR “Sleep Fragmentation” OR “Fragmentation, Sleep” OR “Fragmentations, Sleep” OR “Sleep Fragmentations” OR “Sleep”[Mesh] OR “Sleep, Slow-Wave” OR “Sleep, Slow Wave” OR “Slow-Wave Sleep”; and related population: “Police”[Mesh] OR “Police” OR “Police Force” OR “Police Forces” OR “Police Officers” OR “Officer, Police” OR “Officers, Police” OR “Police Officer”; without date and language restriction. Given the results, it is possible to highlight that officers who work rotating shifts or during the night are exposed to worse sleep quality, greater dissatisfaction with work, low levels of alert, breathing problems and snoring, as well as higher rates of injury and degraded driving performance.